2009
DOI: 10.1097/iae.0b013e318195cb28
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Sclerotomy Leakage and Postoperative Hypotony After 23-Gauge Transconjunctival Sutureless Vitrectomy

Abstract: The risk factors of intraoperative sclerotomy leakage requiring suture placement after 23-gauge transconjunctival sutureless vitrectomy are prior vitrectomy, a young age at operation, and vitreous base dissection. Caution should be exercised to ensure the detection of sclerotomy leakage and hypotony in cases with these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 15 publications
9
90
4
1
Order By: Relevance
“…[7][8][9][10][11] However, there have been questions regarding the self-sealing characteristics and postoperative hypotony in some of the cases. 8,12,13 Previously localized conjunctival and episcleral pigmentation after 20-gauge conventional vitrectomy has been considered owing to a reaction to the sutures used to close the sclerotomy site. 14 Recently, a case of conjunctival pigmentation after 23-gauge MIVS for retinal detachment surgery was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] However, there have been questions regarding the self-sealing characteristics and postoperative hypotony in some of the cases. 8,12,13 Previously localized conjunctival and episcleral pigmentation after 20-gauge conventional vitrectomy has been considered owing to a reaction to the sutures used to close the sclerotomy site. 14 Recently, a case of conjunctival pigmentation after 23-gauge MIVS for retinal detachment surgery was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al reported that sclerotomy sutures were required intraoperatively in 22% out of 92 patients (5). Woo et al performed suture placements in 11.2% of their patients, and found that a younger age (less than 50 years), vitreous base dissection, and history of prior vitrectomy were risk factors for requirement of suture placement (6). The mean age of our patients was 68.12 ± 12.4 and a total of 24 patients were younger than 50 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Our postoperative hypotony incidence is correlated with other series. Woo et al observed postoperative hypotony in 11.3% of cases at 2 h, 6.5% at 5 h, and 3.8% at day 1 (6). It is well known that the level of IOP may change due to diurnal variation.…”
Section: Discussionmentioning
confidence: 99%
“…67 In the 23G technique, hypotony was demonstrated in a range of 3.3-11.3 %, scleral sutures were placed in 11.2-38 % in the various studies. [68][69][70][71][72] In a comparative study, Haas et al showed that post-operative hypotony occurred significantly more often after 23G vitrectomy than after 20G vitrectomy. 73 76 Those authors assumed that open sclerotomies, combined with use of low-flow rate cutters, facilitated the invasion of bacteria to the vitreous cavity.…”
Section: Post-operative Complications Hypotonymentioning
confidence: 99%